Clean Energy Production from Jatropha Plant as Renewable Energy Source of Biodiesel - Kashif Kareem; Maheen Rasheed; Aliha Liaquat; Abu Md Mehdi Hassan; Muhammad Imran Javed; Muhammad Asif (Universitas Pendidikan Indonesia (UPI), 2022)
Population of the world is increasing very rapidly, due to which energy demand is also is increasing unfortunately Pakistan has deficiency of petroleum of reservoir. Pakistan is producing about 64% of its primary energy from fossil fuel which has serious burden on its economy. At the same Pakistan has been blessed by bio-energy production from different types of biomass waste, jatropha is a wild plant which can at any type of land like in Thar, Thal, Cholistan, and other barren land zones. Sample of jatropha raw oil was collected from local market and it was converted into bio-diesel by transesterification process. Purified jatropha oil was used to produced bio-diesel by Transesterification method, Due to transesterification being reversible, excess alcohol is used to shift the equilibrium towards the product. This project can be started in bellow 10 million capital cost and operating cost is about 0.6 million per month. According to our calculation the bio-diesel production cost will be approximately less than Rs. 30 per liter. If the government and concern department focused on the production of jatropha plant and bio-diesel production by jatropha, it will great contribution in saving import expenditures.